Population structure of avian malaria parasites. Issue 13 (17th June 2019) - Humphries, Meghann B.; Stacy, Matthew T.; Ricklefs, Robert E.
Abstract: The geographic distribution of genetic diversity in malaria parasite populations (Apicomplexa: Haemosporida) presumably influences local patterns of virulence and the evolution of host‐resistance, but little is known about population genetic structure in these parasites. We assess the distribution of genetic diversity in the partial Domain I of apical membrane antigen 1 (AMA1) in three mtDNA‐defined lineages of avian Plasmodium to determine spatial population structure and host–parasite genetic relationships. We find that one parasite lineage is genetically differentiated in association with a single host genus and among some locations, but not with respect to other hosts. Two other parasite lineages are undifferentiated with respect to host species but exhibit geographic differentiation that is inconsistent with shared geographic barriers or with isolation‐by‐distance. Additional differentiation within two other lineages is unassociated with host species or location; in one case, we tentatively interpret this differentiation as the result of mitochondrial introgression from one of the lineages into a second lineage. More sampling of nuclear genetic diversity within populations of avian Plasmodium is needed to rule out coinfection as a possible confounding factor. If coinfections are not responsible for these findings, further assessment is needed to determine the frequency of mitonuclear discordance and its implications for defining parasite lineages based on mitochondrial genetic variation. OPEN RESEARCH BADGES: This article has earned an Open Data Badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available at Genbankhttps://www.ncbi.nlm.nih.gov/genbank/, accession numbersMK965548 ‐MK965653 andMK929797 ‐MK930264 . Abstract : Findings here provide a glimpse into the host distribution, spatial distribution, and diversity of avian malaria AMA1 in natural host communities. Complex spatial patterns, differentiation in relation to host genus, and mitonuclear discordance among lineages warrant further investigation to determine the frequency of such introgression events and implications for defining parasite lineages based on mitochondrial genetic variation.